Low-cost Ionospheric Scintillation Detector using Software-based GNSS Receiver - La, The Vinh (Old Journal, 2017)
In this study, we investigate in the use of software-based GNSS receiver to detect ionospheric scintillation in Vietnam. Ionospheric scintillation is well-known for its bad effect on the precision of GNSS receivers. Vietnam locates at a low-lattitude region which is one of the most-affected region if any scintillation occurs. Therefore, it is important to be able detect and store the data of the receiver during scintillation periods for later analysis and mitigation. However, professional ionospheric scintillation monitoring machin are often expensive and not easy to access. The main goal of this work is to propose a low-cost method to detect the scintillation and to save its data for later use by utilizing a software-based GNSS receiver.